Iron deficiency: prevalence, mortality risk, and dietary relationships in general and heart failure populations - Hui Sun; Hui Sun; Qinhong Wang; Wenqiang Han; Changli Chen; Tianyu Wang; Jingquan Zhong; Jingquan Zhong (Frontiers in Cardiovascular Medicine, 2024)
BackgroundIron deficiency (ID) is the most common nutritional deficiency, with little research on its prevalence and long-term outcomes in the general population and those with heart failure (HF). Both the relationships between dietary iron and ID, as well as dietary folate and ID, are understudied.MethodsWe used data from the National Health and Nutrition Examination Survey from 1999 to 2002 to investigate the prevalence, prognosis, and relationship between dietary and ID defined by different criteria in the general population (n = 6,660) and those with HF (n = 182).ResultsThere was no significant difference in the prevalence of ID between HF patients and the general population after propensity score matching. Transferrin saturation (TSAT) <20% was associated with higher 5-year all-cause mortality (HR: 3.49, CI: 1.40–8.72, P = 0.007), while ferritin <30 ng/ml was associated with higher 10-year (HR: 2.70, CI: 1.10–6.67, P = 0.031) and 15-year all-cause mortality (HR: 2.64, CI: 1.40–5.00, P = 0.003) in HF patients. Higher dietary total folate but dietary iron reduced the risk of ID (defined as ferritin <100 ng/ml) in HF patients (OR: 0.80; 95% CI: 0.65–1.00; P = 0.047).ConclusionsThe prevalence of ID was identical in HF and non-HF individuals. Ferritin <30 ng/ml was associated with long-term outcomes whereas TSAT <20% was associated with short-term prognosis in both the general population and HF patients. A diet rich in folate might have the potential for prevention and treatment of ID in HF patients.